2000
DOI: 10.1128/jvi.74.7.3410-3412.2000
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-Depleted Albumin Induces the Formation of Echovirus A Particles

Abstract: Picornavirus infection requires virus uncoating, associated with the production of 135S "A" particles and 80S empty particles from 160S mature virions, to release the RNA genome into the cell cytoplasm. Normal albumin inhibits this process. We now show that when depleted of fatty acids, albumin induces the formation of echovirus A particles.Echoviruses (EVs), members of the Enterovirus genus of the family Picornaviridae, are small positive-strand RNA viruses with icosahedral symmetry which produce a broad spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…3F), and the approximately 1:1 ratio of albumin and fatty acids observed in serum, it seems probable that under physiological conditions, the albumin present outside the cells starts the uncoating process. The ability of faf-BSA to induce echovirus A-particle formation was previously shown using a radioactive gradient; however, the nature of this process was not studied further (21). Our results here explain the mechanism by which faf-BSA induces uncoating in enteroviruses, such as echoviruses and coxsackieviruses.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…3F), and the approximately 1:1 ratio of albumin and fatty acids observed in serum, it seems probable that under physiological conditions, the albumin present outside the cells starts the uncoating process. The ability of faf-BSA to induce echovirus A-particle formation was previously shown using a radioactive gradient; however, the nature of this process was not studied further (21). Our results here explain the mechanism by which faf-BSA induces uncoating in enteroviruses, such as echoviruses and coxsackieviruses.…”
Section: Discussionsupporting
confidence: 56%
“…They have also been found to exist in purified virus preparations (20). One study showed that treatment with fatty acid-free bovine serum albumin (BSA) converts echovirus 12 into A-particles, but the mechanism of action was not investigated further (21). In addition, there are only few studies reporting what effects other physiological factors, such as changes in ionic conditions, may have on the virus particle (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of these components, virus conversion was able to proceed directly to the 80S particle, independent of both temperature and receptor (data not shown), perhaps triggered by a membrane interaction resulting from transient externalization of VP1. Previous studies have documented the ability of BSA (or fatty acid components present in preparations of BSA) or myristate to stabilize picornavirus particles (11,33,34). In the current study, BSA may also have stabilized the virus, leading to reduced virus breathing and therefore reduced nonreceptor-mediated membrane interaction.…”
Section: Discussionmentioning
confidence: 57%
“…Enterovirus breathing is believed to require equilibrium between occupied and empty pockets; i.e., pocket factor must be displaced for the capsid conformation to open (6,7). Albumin is the principal fatty acid-binding protein in serum, and defatted albumin has been shown to promote an echovirus conversion to A-particles and to increase permeability to small molecules (33,35). The measured fatty acid content of the BSA purified from FBS was substantially less than saturating, so the BSA in these experiments has ample reserve capacity to bind fatty acids (36).…”
Section: Fig 14 Cvb3/28 Was Suspended In Pbs (A) Pbs With 20% Fbs (B)mentioning
confidence: 99%